2010
DOI: 10.4055/cios.2010.2.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Inter- And Intra-observer Variability Of A Cervical OPLL Classification Using Reconstructed CT Images

Abstract: BackgroundThe lateral radiograph-based system described by Tsuyama is used widely to classify ossification of the posterior longitudinal ligament (OPLL) of the cervical spine. However, OPLL is a complex 3-dimensional (3-D) lesion, not a simple and uniplanar one, which is often difficult to identify on a lateral radiograph. Furthermore, its reliability among spine surgeons has not been investigated. Given the popularity of a reconstructed computed tomography (CT), this study examined the inter- and intra-observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…Chang et al 6 reported low inter-and intraobserver reliability of lateral radiography as a tool for OPLL classification, particularly for continuous-type OPLL. The inter-and intraobserver kappa values were only 0.51 and 0.67, respectively.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…Chang et al 6 reported low inter-and intraobserver reliability of lateral radiography as a tool for OPLL classification, particularly for continuous-type OPLL. The inter-and intraobserver kappa values were only 0.51 and 0.67, respectively.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…1 To our knowledge, CT imaging has not been used for evaluating the progression of OPLL in any previous study that has included patients who were managed conservatively. Thus, in the present study, we aimed to analyze the progression of cervical OPLL using CT, report on the morphology of OPLL masses, and evaluate the factors associated with mass progression.…”
mentioning
confidence: 99%
“…Multidimensional evaluation of ossification can be achieved with CT images, but it is difficult to evaluate continuity on 2D X-ray images. On 3D images, however, evaluation of continuity and classification of ossification are comparatively simple [19]. With CT images, changes in ossification form and thickness on the caudal side can be evaluated in detail in patients with ossifications growing toward the cranial side.…”
Section: Discussionmentioning
confidence: 99%